Kompetensi dan Tantangan Pendidikan IPS di Indonesia: Pendekatan Kurikulum, Peran Sosial, dan Dinamika Isu Aktual (International Forum of Researchers and Lecturers, 2024)
Social Studies (IPS) is one of the subjects taught at the elementary / MI / SDLB level to SMP / MTs / SMP / SMPLB. IPS examines various claims, facts, assumptions, and generalizations related to social issues, by covering disciplines such as Geography, History, Sociology, and Economics in the SMP / MTs curriculum. Through social studies learning, students are encouraged to become active citizens, caring, politically aware, and have a global awareness and love of peace.This research uses a literature analysis method or literature review approach. Social studies covers a variety of subjects, including science, mathematics, and Indonesian language, thus placing it as a challenging field of study. Social studies learning seeks to answer various human rights issues and daily social problems faced by society. In the process, social studies learning is characterized by challenges and complexities that must be faced by educators and students. Keywords: Social Science, Education and Curriculum, Social and Civic Issues, Literature Review